From Pink-Collar to Lab Coat: Cultural Persistence and Diffusion of Socialist Gender Norms - Naomi Friedman-Sokuler; Claudia Senik (Institute of Labor Economics (IZA), 2020)
The fall of the Iron Curtain in 1989 led to a massive migration wave from the Former Soviet Union (FSU) to Israel. We document the persistence and transmission of the Soviet unconventional gender norms, both vertically across generations of immigrants, and horizontally through neighborhood and school peer effects. Tracking the educational and occupational choices of a cohort of young Israeli women, we identify the persistence of two important features of the Soviet culture: the prioritization of science and technology, and the strong female attachment to paid-work. Women born in the FSU, who immigrated in infancy, are significantly more likely than natives and other immigrants to major in STEM in high school. In tertiary education, they remain over-represented in STEM, but also differ significantly from other women by their specific avoidance of study fields leading to "pink collar" jobs, such as education and social work. They also display a specific choice of work-life balance reflecting a greater commitment to paid-work. Finally, the choice patterns of native women shift towards STEM and away from traditional female study fields as the share of FSU immigrants in their lower-secondary school increases.
Keywords: Z1; I21; J16; J24; P30; 330; culture; gender norms; education; STEM; occupational choice; immigration; Soviet Union; Israel